Establishment of Average Body Measurement of Male Adolescents in Benue State, Nigeria - A., Edache; E.A., Akpan (Journal of Home Economics Research, 2024)
The study established average body measurement of male adolescents in Benue State. Survey research design was used for the study. A sample of three hundred (300) male adolescents were proportionally selected from secondary schools. Measurements were taken from 17 parts of adolescents body using none stretch tailors’ tape. Major findings of the study include identification of body characteristics of adolescents and establishment of mean body measurement in 3 size categories of small, medium and large.